Clinical and Biochemical Profile of Obstructive Urolithiasis in Sheep - Maciel, Thiago Arcoverde; Ramos, Inalda Angelica [UNESP]; Silva, Rafael Jose da; Soares, Pierre Castro; Dantas Carvalho, Cleyton Charles; Souto Maior Junior, Rinaldo Jose de; Amoroso, Lizandra [UNESP]; Baraldi Artoni, Silvana Martinez [UNESP]; Bastos Afonso, Jose Augusto; Oliveira, Daniela (Univ Fed Rio Grande Do Sul, 2017)
Background: Urolithiasis is a metabolic disease of complex and multifactorial etiology, characterized by uroliths formation in the urinary system. It becomes clinically important when obstruction occurs, with little chance of reversal of the situation, and prevention is the best option for maintaining the integrity of the reproductive capacity. For this, the aim of this research was to know the clinical and biochemical profile of urolithiasis and predict the evolution of the disease in Santa Ines sheep breed fed with calculogenic diet, as well as to evaluate the prevention potential of vitamin C. Materials, Methods & Results: In this study, 14 healthy male Santa Ines sheep, aged approximately 90 days, were divided into two groups (G1- without vitamin C and G2 - with vitamin C, 1 g/dayly/orally) fed on calculogenic diet for 120 days. The animals were examined weekly, including observation of clinical signs, and blood and urine analysis were performed. Final leukogram revealed leukocytosis by neutrophilia in G2. There was aciduria in 57.14% (G1) and 71.43% (G2) and the presence of blood cells, bacteria and sperm to the urinary sediment. There were hyperproteinemia and proteinuria, but no significant elevation in serum albumin and globulin, urea and creatinine concentrations. Urine urea remained high. Serum uric acid was higher in M15 and M16, although inferior to those obtained in urine. No hyperglycemia was reported and urine concentrations remained stable over time, with a peak observed at M16. Serum AST presented a significant increase in M12 and M13, but returned to normal just after. Urine revealed significant turbidity and density changes for G1 and G2. Haematuria was observed in G1 and G2; however, changes in color and odor were evidenced only in G2. It was verified that, although most of the animals presented aciduria, 42.86% of G1 and 28.57% of G2 presented alkaline urinary pH. Crystals found in both groups were amorphous phosphate, calcium carbonate, triple phosphate and calcium phosphate. Discussion: High-grain diet becomes a risk factor to the development of the disease, even face to high water consumption. The confinement condition, associated to the hyperprotein diet and high phosphorus levels characterized by the large supply of concentrate to which the animals were submitted, are implicated as risk factors for the disease development. Urinary acidification is cited as an efficient alternative for the prevention of formation of struvite calculous and calcium phosphate, happened often in sheep species, so vitamin C was used. Clinical characteristics of urolithiasis are related to the location/degree of obstruction and time elapsed from obstruction to clinical care, and may begin abruptly with anorexia, colic, depression, strangulation with oliguria, hematuria or anuria. Intensity and manifestation of clinical signs of urolithiasis is dependent on the occurrence and degree of obstruction as a result of pain and consequent metabolic disorders. The design of the biochemical profile has been shown to be effective in elucidating the behavior of renal function biomarkers, such as urea and creatinine over of the process of calculus formation and installation of the disease. Presence of crystals, flaking cells and other elements such as cylinders can cause an increase in urinary density. Although the urinary pH of herbivores is naturally alkaline, it varies according to the animal's diet. Though the perceptual of the urinary acidification superior on G2, it did not prove to be effective in preventing the development of obstructive urolithiasis, which occurred in 28.57% (2/7) of the animals that received vitamin C. Thus, other concentrations should be tested, with possibility of success and favorable conditions (economic and palatability) than the current acidifier.
Keywords: sheep disease; metabolism; urinary tract; acidification; urine